Digitally connected. Forms of political participation by young people in Lower Austria - Ajanović, Edma; Fritsch, Katharina; Zahorka, Florian (Momentum Quarterly, 2021)
Against the background of post-Fordist transformations and the few studies that provide information about the situation in Austria, in this article we analyze the relationship between digital forms of political participation and traditional forms of political and media representations of youth. We explore our question from a frame-analytic perspective, drawing on data we collected through a media analysis and participatory ethnography in the context of the municipal elections 2020 in Lower Austria. We discuss (self-)representations and youth political participation along three dimensions: Youth and local politics, youth and climate, and youth as digital actors. In this regard, we show that youth’s political practices are predominantly shaped by latent forms of participation – offline and online – highlighting the role of memes as digital practice. Our article contributes to the question of how public spheres are created in the age of digital platforms and how young people contribute to them. Based on our findings we emphasize the much-discussed tendency of an individualization of political participation in the context of digitalization.
Keywords: political participation; youth; political representation; digitalization; media